Hierarchical regulation of sensor data transmission for networked telerobots - Martínez-Tenor, Ángel; Gago-Benítez, Ana; Fernández-Madrigal, Juan Antonio; Cruz-Martín, Ana María; Asenjo-Plaza, Rafael; González-Navarro, María Ángeles (My University, 2014)
Networked telerobots carry sensors that send data, with stochastic transmission times, to a remote human operator, who must execute some real-time control task (e.g., navigation). In this paper we propose to regulate the sensory information being transmitted in order to guarantee soft real-time requirements and also optimize the quality of control, through a novel two-level hierarchical controller that both varies the amount of transmitted sensor data and dynamically reconfigures active sensors. Our controller has been implemented in a web-based teleoperator interface that is highly portable (it runs on desktop PCs, tablets, smartphones, etc.) and non-invasive, i.e., requires minimal modifications in the existing components of the system, thus being suitable for many applications. Here we present our regulation methods and the results of some experiments. They demonstrate the maximization of the transmitted data while guaranteeing the real-time requirements.
Keywords: Autómatas - Sistemas de control; Networked sensors; Real-time communications; User interfaces